The Application of Kinemaster as a Learning Media for Indonesian Language Class IV in Covid-19 Period - Hanif, Muhammad; MoHa, luqman; Anugerah , Ghifari Fajar (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. The kinemaster application can help someone or can make it easier for someone to produce good videos. Online learning really needs this application because students are now learning using cellphones and like to watch YouTube, so teachers can display this video creatively with physical learning material. At this time many people change their profession to become YouTubers, because this profession is very promising according to them and can guarantee their lives. Nowadays we find many youtubers. Many people today are competing to create their content, they are willing to play around and ruin people's moods. Purpose. This application aims to facilitate teachers in making various learning media. Almost everyone uses applications to work that function as the utilization of this sophisticated technology. Method. This article The method used in this research is a qualitative method, because qualitative methods are very flexible and accurate. Results. The result of this study is that the kinemaster application is very suitable for use as a learning media in class IV because the media is interesting and able to increase students' enthusiasm for learning. Conclusion. The use of kinemaster helps teachers in solving the problem of students who are reluctant to learn, because in general students really like to learn while doing. Hopefully in the future students will be more enthusiastic in learning.